Lowriders in space - Camper, Cathy; 1976- (San Francisco, California : Chronicle Books, 2014)
Lupe Impala, El Chavo Flapjack, and Elirio Malaria love working with cars. You name it, they can fix it. But the team's favorite cars of all are lowriders - cars that hip and hop, dip and drop, go low and slow, bajito y suavecito. The stars align when a co
V.1. Lowriders in space
"Book 1."
Spanish words and phrases used throughout English text.
GN430L
Decoding: 4 (hard) Vocabulary: 5 (very hard) Sentences: 4 (hard) Patterns: 5 (very hard)
Accelerated Reader
Texas Bluebonnet Award Nominee 2016-2017.
Keywords: Lowriders -- Comic books, strips, etc; Competition (Psychology) -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Mexican Americans -- Comic books, strips, etc; Lowriders -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; Friendship -- Juvenile fiction; Mexican Americans -- Juvenile fiction; Graphic novels; Lowriders -- Fiction; Competition (Psychology) -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction; Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION -- Comics & Graphic Novels; JUVENILE FICTION -- Science & Technology; JUVENILE FICTION -- Transportation -- Cars & Trucks; Mexican Americans; Competition (Psychology); Friendship; Lowriders; Lowriders -- Fiction; Competition (Psychology) -- Fiction; Friendship -- Fiction; Mexican Americans -- Fiction; Comic books, strips, etc; Graphic novels; Graphic novels; Fictional Work; Graphic novels, Children's.; Juvenile works; Comics (Graphic works); Fiction; Graphic novels; Juvenile works; Comic books, strips, etc; Graphic novels; Comics (Graphic works); Fiction; Dust jackets (Binding) -- 2014.; Romans; Graphic novels